Olanzapine induces weight gain in offspring of prenatally exposed poly I:C rats by reducing brown fat thermogenic activity - Chen, Xiaoying; Liu, Lu; Zeng, Yanping; Li, Dejuan; Liu, Xuemei; Hu, Changhua (Frontiers in Pharmacology, 2022)
Background: Olanzapine (OLZ) is an antipsychotic with a high risk of metabolic syndrome, and its induced metabolic disturbance may be related to the thermogenic function of brown adipose tissue (BAT). Of note is that schizophrenia itself appears to be associated with a higher incidence of metabolic syndrome. However, whether OLZ affects metabolic disorders by regulating BAT function and its mechanism in animal models of schizophrenia have not been reported. Methods: We induced maternal immune activation (MIA) in pregnant rodents by injection of synthetic double-stranded RNA-poly I:C (a virus-like substance), and rats were injected with poly I:C, 10 mg/kg) or saline on day 13 of gestation. Rat offspring received OLZ (1 mg/kg, tid) or vehicle from adulthood for 28 days, and body weight and food intake were recorded. Morphological alterations of white adipose tissue (WAT) and BAT were analyzed by HE and oil red staining, and expression of BAT-specific marker proteins/genes was detected by western blot and qRT-PCR. In addition, embryonic stem cells C3H10T1/2 were used to direct differentiation into brown-like adipocytes, and C3H10T1/2 cells were treated with OLZ for the differentiation process. The effects of OLZ on brown-like adipocyte differentiation and activity were analyzed using oil red staining, immunofluorescence and flow cytometry. Results: Compared with the Veh (saline) group, the TG, pWAT weight, adipocyte size and liver weight of the Veh (poly I:C) group were significantly increased, suggesting that the offspring of Poly I:C rats had obvious dyslipidemia and lipid accumulation, which were risk factors for metabolic abnormalities such as obesity. In addition, OLZ treatment resulted in altered WAT and BAT morphology in poly I:C or saline exposed offspring, causing lipid accumulation and weight gain and reducing the expression of the BAT-specific marker molecule UCP1 protein/gene. At the same time, OLZ inhibited the directional differentiation and mitochondrial activity of C3H10T1/2 brown-like adipocytes. Conclusion: Poly I:C-elicited MIA and OLZ differentially inhibited BAT activity and mitochondrial biogenesis, leading to weight gain in adult rats, a process involving PPAR-γ/UCP1-related thermogenic proteins.